(Post-)crisis policing, public health and private security: the COVID-19 pandemic and the private security sector - Leloup, Pieter (Policing and society, 2022)
While the role of the public police in the law enforcement-public health (LEPH) nexus has received increased attention in recent years, much less is known about the involvement of private security actors in this field. However, understanding the new and shifting roles of private security companies in LEPH is vitally important. During the COVID-19 pandemic, the security industry witnessed increased demands for health-care related services worldwide. This article explores the effects of the crisis on the provision of private security, by investigating the intersections between private policing and public health throughout the pandemic. With specific attention to the emergence of private security in the field of LEPH, the impact on the operations (e.g. disruptions in resources, temporary unemployment), and services (e.g. use of technological innovations such as fever screening, policing COVID-19, monitoring public health) are considered in greater detail. The findings contribute to the understanding of private security provision where public health, safety and security intersect. Important new insights are offered on the impact of the public health crisis on (the concept of) private security, and consideration is made relating to the longer-term role of the industry in the context of the crisis’ transforming potential of the policing landscape.